The Importance of Public Reason in Democratic Society and the Criticism of Rawls’s Concept of Unreasonableness - Sunaryo, Sunaryo (Peminat Ilmu Ushuluddin, 2023)
People everywhere always live in diversity. Sometimes, people express their values in ways incompatible with the principle of reciprocity or reasonableness. In John Rawls's view, they are categorized as unreasonable because their expression does not align with public reason. In this article, we need to ask, are they really unreasonable and a threat to democracy? Here, we state that public reason is essential to democracy. However, we also need to build a fairer public life and broader public reasoning that engages people from wider background cultures. Thus, Rawls’ understanding of unreasonableness is challenging. We cannot exclude people who have not applied public reason from public life. We neither categorize them as unreasonable because they do not necessarily attack public reason. We can identify them as “in-between” reasonable and unreasonable people, and they are not really a threat to democracy. We need to engage and endorse them to explore a just public life. In order to build a fairer public life, we need to engage people widely and make public reasoning a place for learning the meaning of justice.